Cover Feature: Nanocatalysts Unravel the Selective State of Ag (ChemCatChem 11/2020). Issue 11 (18th May 2020) - Lamoth, Maximilian; Jones, Travis; Plodinec, Milivoj; Machoke, Albert; Wrabetz, Sabine; Krämer, Michael; Karpov, Andrey; Rosowski, Frank; Piccinin, Simone; Schlögl, Robert; Frei, Elias
Abstract : The Cover Feature shows an ensemble of Ag atoms differently enriched with oxygen for the ethylene epoxidation reaction. In their Full Paper, M. Lamoth et al. demonstrate that the oxygen concentration in/on Ag defines the selectivity of the Ag catalysts. Ethylene epoxide is preferentially formed on oxygen poor Ag. This effect is directly coupled to the oxophilicity of Ag, which is increased for Ag nanoparticles. These results clarify the selective state of Ag with respect to the oxygen concentration/interaction and offer a route to a catalyst design perspective. More information can be found in the Full Paper by M. Lamoth et al.